Early changes in cerebral metabolism after perinatal hypoxia-ischemia: a study in normothermic and hypothermic piglets - Andelius, Ted C. K.; Bøgh, Nikolaj; Pedersen, Mette V.; Omann, Camilla; Andersen, Mads; Andersen, Hannah B.; Hjortdal, Vibeke E.; Pedersen, Michael; Rasmussen, Martin B.; Kyng, Kasper J.; Henriksen, Tine B. (Frontiers in Pediatrics, 2023)
Hypoxic ischemic encephalopathy (HIE) after a perinatal insult is a dynamic process that evolves over time. Therapeutic hypothermia (TH) is standard treatment for severe to moderate HIE. There is a lack of evidence on the temporal change and interrelation of the underlying mechanisms that constitute HIE under normal and hypothermic conditions. We aimed to describe early changes in intracerebral metabolism after a hypoxic-ischemic insult in piglets treated with and without TH and in controls. Three devices were installed into the left hemisphere of 24 piglets: a probe measuring intracranial pressure, a probe measuring blood flow and oxygen tension, and a microdialysis catheter measuring lactate, glucose, glycerol, and pyruvate. After a standardized hypoxic ischemic insult, the piglets were randomized to either TH or normothermia. Glycerol, a marker of cell lysis, increased immediately after the insult in both groups. There was a secondary increase in glycerol in normothermic piglets but not in piglets treated with TH. Intracerebral pressure, blood flow, oxygen tension, and extracellular lactate remained stable during the secondary increase in glycerol. This exploratory study depicted the development of the pathophysiological mechanisms in the hours following a perinatal hypoxic-ischemic insult with and without TH and controls.